Association between Body Fat and Diabetic Peripheral Neuropathy in Middle-Aged Adults with Type 2 Diabetes Mellitus: A Preliminary Report - Oh, Tae Jung (J Obes Metab Syndr, 2019)
BACKGROUND: Previous epidemiologic studies showed that obesity increased the risk of diabetic peripheral neuropathy (DPN). However, there is very limited data about the impact of body fat measured by body composition analysis in DPN. METHODS: Subjects with type 2 diabetes mellitus (T2DM) between 20 to 55 years old were enrolled. DPN was diagnosed using the Michigan Neuropathy Screening Instrument. Body composition was assessed by bio-impedance analysis, and the association between body composition and DPN was investigated. RESULTS: Among 65 subjects, 44.6% were diagnosed with DPN. Subjects with DPN had higher body mass index and waist circumference than subjects without DPN. Body composition data showed that fat mass, fat percent, and visceral fat area were higher in subjects with DPN than in subjects without DPN. Furthermore, the presence of DPN was associated with waist circumference (odds ratio [OR], 1.151; 95% confidence interval [CI], 1.055–1.256; P=0.002), visceral fat area (OR, 1.026; 95% CI, 1.005–1.048; P=0.015), and insulin resistance (OR, 1.673; 95% CI, 1.091–2.565; P=0.018) after adjusting age, sex, diabetes duration, and smoking status. CONCLUSION: Abdominal obesity was associated with DPN. Insulin resistance might mediate obesity and DPN in middle aged subjects with T2DM.